Hypercube optimization based global solution in numerical benchmark and sensor localization - R.Sujatha, S; Siddappa, M (International Journal of Engineering and Technology, 2018)
An original learning algorithm for solving global numerical optimization problems is proposed. The proposed algorithm is strong stochastic search method which is based on evaluation and optimization of a hypercube and is called the hypercube optimization (HO) algorithm. The hypercube optimization algorithm includes the initialization and evaluation process, and searching space process. The designed HO algorithm is tested on specific benchmark functions. The comparative performance analysis have made against with other approaches of dynamic weight particle swarm optimization and self-adaptive differential evolution algorithm. Convergence characteristics of self-adaptive differential evolution algorithm has deliver the much better functionalÂ Â value in compare to dynamic weight based particle swarm optimization.